General Approach to Amides through Decarboxylative Radical Cross-Coupling of Carboxylic Acids and Isocyanides; Organic Letters; Vol. 26, iss. 16 - Qing Yan; Qing-Jia Yuan; Shatskiy A. Andrey; Alvey G. R. Gregory; Stepanova E. V. Elena Vladimirovna; Jian-Quan Liu; Karkas M. D. Markus; Xiang-Shan Wang (2024, 2024)
Title screen